Synaptic proteins in CSF relate to Parkinson’s disease stage markers - Erika Bereczki (Nature Portfolio, 2017)
Biomarkers: Synaptic proteins give it away The levels of synaptic proteins in the cerebrospinal fluid (CSF) correlate with Parkinson’s disease (PD) severity. Dysfunctional communication between nerve cells is an established hallmark of early stage PD and other neurodegenerative disorders. As synapses are lost from various brain areas synaptic proteins leak into the CSF, but little is known about how their concentration correlates with disease stage and prognosis. Erika Bereczki and colleagues at the Karolinska Institutet in Sweden measured the concentration of three synaptic proteins in the CSF of 52 patients with PD and 87 controls. They found that the levels of two of them (neurogranin and SNAP25) correlated with the severity of both motor and non-motor symptoms. Further work will determine whether these proteins could aid early detection of PD and help predict disease progression.